Monitoring osmotic pressure with a hydrogel integrated optofluidic microlaser - Jie, Randall Ang (2023)
Osmotic pressure plays a key function in many biological systems and biointerfaces; however, it is often challenging to monitor minute osmotic changes from the micron to the nanoscale. Unlike conventional methods, which mostly rely on measurements of deformations, here we proposed a method to detect osmotic pressure by analysing laser emission from dye-doped hydrogel droplets encapsulated in a Fabry-Pérot optical micro-resonator. Taking advantage of enhanced light-matter interactions, subtle osmotic changes were revealed through lasing wavelength shifts as a result of the optical path length difference. Dynamic monitoring of osmotic pressures was also recorded through lasing spectra. Finally, we showcase how the spatial information in the form of transverse modes could provide information related to refractive index distribution and three-dimensional structural changes of hydrogel droplets due to osmotic pressure. The ability to detect osmotic pressure with optofluidic lasers illuminates the potential for on-chip sensing of body fluids and cellular environments.